The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5530/ijper.56.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Thiazoles: A Retrospective Study on Synthesis, Structure-activity Relationship and Therapeutic Significance

Abstract: Thiazole or 1,3-thiazole is a distinct heterocyclic compound which incorporates sulphur and nitrogen atoms. It is a vital framework present in numerous pharmacologically active compounds, be it of natural origin or of synthetic nature. Many thiazoles having antitumor and antiviral activities, originate from microbes and marine organisms. A variety of synthetic drugs, having thiazole group, like antimicrobial sulfathiazole, antibiotic penicillin, antidepressant pramipexole, antineoplastic agent bleomycin, antir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…This suggests a potential advantage of IsoB in achieving cytotoxic effects at substantially lower concentrations and within a shorter timeframe. In addition, the CC 50 value for IsoB falls well within the lower part of the range of respective concentrations of other isothiazolones determined for their in vitro cancer cytotoxicity [15,38,39]. In particular, the observed effect on cell viability of IsoB with 3.54 µg/mL CC 50 (16.3 µM) is comparable to those reported by Lu et al [40] and Zaharia et al [14] against various cancer lines.…”
Section: Discussionsupporting
confidence: 84%
“…This suggests a potential advantage of IsoB in achieving cytotoxic effects at substantially lower concentrations and within a shorter timeframe. In addition, the CC 50 value for IsoB falls well within the lower part of the range of respective concentrations of other isothiazolones determined for their in vitro cancer cytotoxicity [15,38,39]. In particular, the observed effect on cell viability of IsoB with 3.54 µg/mL CC 50 (16.3 µM) is comparable to those reported by Lu et al [40] and Zaharia et al [14] against various cancer lines.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, this scaffold could represent a new structural element that is useful for discovering novel pharmacological tools in treatment to target 5HTR [20][21][22]. Simultaneously, it was already reported that thiazole-containing compounds have been developed as possible inhibitors of several targets involved in biochemical and oncogenic regulatory pathways, including enzyme-linked receptors located on the cell membrane (polymerase inhibitors) and cell cycle (microtubular inhibitors) [23,24]. Hence, we investigated the cytotoxic activity of novel thiazolinylphenyl-piperazines (2a-c and 3a-c) against LNCAP (androgen sensitive), DU145 and PC3 (androgen independent) prostate cancer cells, and MCF7 (ER+, PR+, HER2−), SKBR3 (ER−, PR+, HER2+) and MDA-MB231 (ER−, PR−, HER2−) breast cancer cell lines (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…1,3-Thiazoles, which derived from thiosemicarbazone derivatives, is also known for its various pharmacological applications, as its scaffold is useful for several natural, non-natural and semi-synthetic drugs, including anti-inflammatory, anti-parasitic and antineoplastic properties [ 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Numerous studies suggested that medications such as Tiazofurin, Dasatinib, and Dabrafenib that contain thiazoles may have anticancer properties against different cancer types ( Figure 1 ) [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%